Formation of Few‐ and Monolayered WS2 Sheets Using Plasma‐Treated Dimethyl‐Sulfoxide Solvent‐Based Exfoliation. Issue 2 (12th September 2019) - Esfandiari, Mehrnaz; Kamaei, Sadegh; Rajabali, Mona; Mohajerzadeh, Shams
Abstract : Tungsten disulfide is an emerging 2D material with unique electrical and optical properties. Although chemical vapor deposition and mechanical exfoliation lead to large‐area layers, sonication solvent‐based exfoliation is a convenient method to realize mono‐ and few‐layer flakes. Herein, a mixture of dimethyl‐sulfoxide (DMSO) and water as a safe, facile, and user‐friendly exfoliation solvent for the synthesis of large‐scale WS2 sheets is investigated. While water molecules weaken the Van der Waals force between the stacked layers, DMSO molecules facilitate the exfoliation process. To improve exfoliation and achieve large‐area sheets, plasma pretreatment is exploited on bulk WS2 prior to the exfoliation process. For this purpose, O2 and H2 gases are used to carry out the plasma pretreatment. The oxygen plasma treatment is shown to be an effective strategy, leading to large‐area features. Moreover, inert gases as He and Ar are used to obtain small sheets. Transmission electron microscopy, atomic force microscopy, Raman spectroscopy, and dynamic light scattering analyses are used to understand the mechanism of exfoliation and study the effects of various parameters as water temperature, plasma power, and duration. Abstract : Large‐area WS2 sheets are realized using plasma‐assisted liquid exfoliation. The use of oxygen for plasma treatment of the WS2 grains prior to exfoliation leads to the formation of large‐area few‐ or monolayered flakes. On the contrary, the use of helium for plasma treatment results in thin and small flakes. High‐performance photodetectors are realized and tested using O2 ‐treated WS2 sheets.